On the Threshold of Exact Science : Selected Writings of Anneliese Meier on Late Medieval Natural Philosophy - Maier, Annelise (The Middle Ages Series, 2016)
Translated into English for the first time, the writings of the twentieth-century scholar Annelise Maier on late medieval natural philosophy are here made accessible to a broader audience. The seven selections represent both Maier's earlier and later works. Her perceptions as a trained philosopher, coupled with her familiarity with the full range of primary source material, result in these rare insights into the historical importance of medieval science.